O-260 Improved implantation and pregnancy rates in frozen-thawed embryo transfer using a modified-natural ovulatory regimen. (30th June 2022) - Rodrigues, R; Setti, A; Braga, D; Guilherme, P; Iaconelli, A.; Borges Junior, E
Abstract: Study question: Are the outcomes of pregnancy significant different between modified-natural (mN) cycle frozen‐thawed embryo transfer (FET) and hormone terapy (HT) cycle FET? Summary answer: Implantation and pregnancy rates are significantly higher in mN cycle FET as compared to HT cycle FET. What is known already: The use of FET has dramatically increased the cumulative pregnancy rate and reduced the cost and time to pregnancy in assisted reproductive technology (ART). Three different regimens can be used to perform FET, the spontaneous ovulatory (natural) cycle; the one in which the endometrium is artificially prepared with HT; and cycles in which ovulation is induced. In our center, for the past three years, we have performed HT cycle FET as well as a modified-natural regimen, which includes the administration of 250 µg recombinant hCG (r-hCG) upon the visualization of one follicle measuring ≥ 18 mm in diameter. Study design, size, duration: Women undergoing FET post intracytoplasmic sperm injection (ICSI), between Jan/2019 and August/2021 in a private university-affiliated IVF center were included (mN cycle FET group, n = 142 and HT cycle FET group, n = 1180). Generalized linear models adjusted for potential confounders, followed by Bonferroni post hoc were used to compare clinical outcomes between groups. Participants/materials, setting, methods: In mN cycle FET group, after menses, the endometrial development was monitored, and patients received 250µg r-hCG upon the visualization of one follicle ≥ 18mm in diameter, and 600mg daily of micronized progesterone for five days, until embryo transfer. In HT cycle FET group, after menses the patients received 200µg of transdermal 17 β-estradiol every three days. When endometrium showed proliferative morphology and thickness of at least 7.5mm, 600mg of progesterone was daily administered. Main results and the role of chance: Mean female age was similar between the groups (36.0 years ± 0.5 for mN cycle FET and 35.6 years ± 0.2 for HT cycle FET groups, respectively). The implantation rate was significantly higher in mN cycle FET group compared to HT cycle FET group (45.3% ± 0.76 vs. 38.6% ± 0.22, p < 0.001, respectively). The pregnancy rate was also significantly higher in mN cycle FET group compared to HT cycle FET group (66.0% vs. 52.4%, p = 0.017, respectively). No significant differences were observed between the groups in miscarriage rate (10.7% for mN cycle FET and 15.7% for HT cycle FET groups, respectively, p = 0.279). Limitations, reasons for caution: Retrospective nature of this study and the small sample size may be a reason for caution. Wider implications of the findings: Our study suggests use of an hCG trigger may improve outcomes in natural cycle FET. In patients undergoing FET, triggering ovulation can significantly reduce the number of visits necessary for scheduling embryo transfer without an adverse effect on outcomes. Ovulation triggering can increase both patient convenience and cycle cost effectiveness. Trial registration number: Not applicable